The reunions of Odysseus in Ithaca - Reboreda Morillo, Susana (2018)
The myth of Odysseus could be described as one of the closest to the human being, of all that bequeathed us the Greek antiquity. Human, because Odysseus seeks, struggles and suffers because he loves like the human being. It is very human, because we can not separate in this myth the vicissitudes of his faithful wife Penelope; of his son Telemachus; of his father Laertes; of his mother Anticlea, dead of pain by the absence of that one; of his nurse Euriclea; of his swineherd Eumeo; of the magician Circe, who transforms men into animals; the nymph Calypso, who offers divine immortality to Odysseus; the sweet and pure Nausicaa, next to which Odysseus could have had a peaceful new home in the country of happy men, the Phaeacians. All of them are characters of deep humanity, including if you could say Argos, that little animal that waited twenty years to reach to see its owner back and give him a last show of love and good death: Disguised Odysseus, when Argos recognizes him he let his death take it away, then turned his gaze away and wiped away a tear. That tear that was denied them to the gods of Olympus was only granted to their old dog Argos.